Impact of Age, Gender, post infection and post vaccination status on antibody response in COVID 19 patients - Sadiq, Sidra; Khan, Maria; Sadiq, Tayyaba; Orakzai, Sheryar; Muhammad Dawood, Mirza; Ul Haq, Najeeb (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate severe acute respiratory syndrome coronavirus-2 spike protein antibodies against coronavirus disease-2019 in post-infection and post-vaccinated individuals. Method: The cross-sectional study was conducted June, 1 to July 31, 2021, at the Rehman Medical Institute, Peshawar, Pakistan, and comprised subjects of either gender in whom immunogenicity was checked 35 days post-vaccination and 90 days post-infection. Correlation with age and gender was checked. Specimens were collected and investigated for severe acute respiratory syndrome coronavirus-2 spike protein antibodies by consuming electro-chemiluminescence immunoassay. Data was analysed using SPSS 23. Results: Of the total 256 patients enrolled, 70(27.34%) were included; 49(69%) males and 21(29.6%) females. The overall mean age was 44±7.75 years. Among 30(42.8%) patients with positive polymerase chain reaction test, the mean time between positive the test and antibody screening was 90±30 days. Among the 40(57.2%) vaccinated individuals, the time between vaccination and antibody screening was 35±9.74 days. Overall, 68(97%) patients revealed robust positive findings to severe acute respiratory syndrome coronavirus-2 spike proteins antibodies >50IU/mL. Male subjects had significantly higher immunogenic response compared to females (p=0.001), and immunogenicity decreased with advancing age (p<0.001). Also, post-vaccinated patients’ antibody response was significant compared to post-infection patients’ response (p=0.001). Conclusion: Majority of the patients had significantly higher antibody titers against severe acute respiratory syndrome coronavirus-2 post-infection and post-vaccination. Males and younger individuals developed a significant humoral immunity compared to females and the elderly. Key Words: Antibodies, COVID-19, SARS-CoV-2, Vaccination.